Impact of Chia Flour on the Nutritional and Rheological Properties of Wheat Flour Blends and Dough - Wojciechowicz- Budzisz, Agata (Wpływ mąki z nasion chia na właściwości odżywcze i reologiczne mieszanek mąki pszennej i ciasta, 2024)
Aim: This study aimed to evaluate the effects of incorporating ground chia seed (chia flour, CF) in varying proportions (0/100, 5/95, 10/90, 15/85, 20/80, and 25/75 w/w chia/wheat flour) on the rheolo-gical and pasting characteristics of blends made with two types of wheat flour (types 650 and 750). Methodology: In the analysed mixtures of wheat flour and chia flour, the total protein content was determined using the Kjeldahl method, and then the properties of starch and the activity of amylolytic enzymes were assessed using an amylograph. Additionally, the Mixolab 1 device was used to analyse the rheological properties of the dough, including its behaviour during mixing and the quality of starch and protein. Results: Adding CF, a rich source of protein, fibre, and healthy fats, increased both total protein content and initial gelatinization temperature in the blends. However, it also extended dough develop-ment time, decreased dough stability, and reduced susceptibility to retrogradation. Implications and recommendations: The addition of chia flour has a positive effect on the techno-logical value of dough, therefore it is recommended to add it in amounts even greater than 10%. Originality/value: This study provides new insights into the impact of chia flour on dough rheology, expanding current knowledge on functional ingredients in bakery applications. The findings contribute to the development of innovative, health-oriented wheat-based products enriched with high-value nutrients.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2024, Nr 40, s. 43-52